2019
DOI: 10.1007/s13280-019-01300-z
|View full text |Cite|
|
Sign up to set email alerts
|

Status and trends of circumpolar peregrine falcon and gyrfalcon populations

Abstract: The peregrine falcon (Falco peregrinus) and the gyrfalcon (Falco rusticolus) are top avian predators of Arctic ecosystems. Although existing monitoring efforts are well established for both species, collaboration of activities among Arctic scientists actively involved in research of large falcons in the Nearctic and Palearctic has been poorly coordinated. Here we provide the first overview of Arctic falcon monitoring sites, present trends for long-term occupancy and productivity, and summarize information desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…Many peregrine falcon populations (especially in Alaska, parts of Canada and northern Fennoscandia) have now largely recovered from dramatic reductions due to pesticide contamination during the 1970s (Franke 2020;this volume). Overall, Arctic peregrine populations now appear stable, with reports of a northward expansion among peregrines in Northwest Greenland (Burnham et al 2012), as well as an advancing timing of breeding in several Arctic regions (Franke 2020), likely as a consequence of climate change.…”
Section: Carnivoresmentioning
confidence: 99%
See 1 more Smart Citation
“…Many peregrine falcon populations (especially in Alaska, parts of Canada and northern Fennoscandia) have now largely recovered from dramatic reductions due to pesticide contamination during the 1970s (Franke 2020;this volume). Overall, Arctic peregrine populations now appear stable, with reports of a northward expansion among peregrines in Northwest Greenland (Burnham et al 2012), as well as an advancing timing of breeding in several Arctic regions (Franke 2020), likely as a consequence of climate change.…”
Section: Carnivoresmentioning
confidence: 99%
“…Many peregrine falcon populations (especially in Alaska, parts of Canada and northern Fennoscandia) have now largely recovered from dramatic reductions due to pesticide contamination during the 1970s (Franke 2020;this volume). Overall, Arctic peregrine populations now appear stable, with reports of a northward expansion among peregrines in Northwest Greenland (Burnham et al 2012), as well as an advancing timing of breeding in several Arctic regions (Franke 2020), likely as a consequence of climate change. Gyrfalcon populations are also stable, although poaching is an increasing concern in some areas (Potapov 2011), and shrubification and a shrinking High Arctic climate zone may pose challenges in the future, mediated through impacts on their primary prey, ptarmigan (Booms et al 2011).…”
Section: Carnivoresmentioning
confidence: 99%
“…For the top avian predators, Franke et al (2020) provided the first overview of monitoring sites for gyrfalcons and peregrine falcons. The authors analyzed long-term trends in occupancy and productivity and summarized information for recommended CBMP FEC attributes.…”
Section: Birdsmentioning
confidence: 99%
“…Ptarmigan populations have been monitored at over 90 sites, with about half of them still being monitored (Fuglei et al 2020). Peregrine falcon and/or gyrfalcons are monitored at 24 sites (Franke et al 2020). Waders and geese are monitored at many sites across the Arctic, but since these taxa are often gregarious at migration stopover and wintering sites, data on population trends are also supported by monitoring efforts outside the Arctic (CAFF 2018a).…”
Section: Birds: Monitoring Statusmentioning
confidence: 99%
“…Percent changes of HII score per ha between 2012 and 2017 in each NP were also calculated to assess whether they were changing or not, and if they were, to discuss options for limiting their effects. Other HF studies in Mexico 26 , Ecuador 27 and Tibet 28 have shown that the HF has caused natural habitat degradation even inside protected areas, and even where unfavorable physical conditions such as high elevation and steep terrain hinders human activities 29 , 30 .…”
Section: Introductionmentioning
confidence: 99%